Genetic linkage of pfmdr1 with food vacuolar solute import in Plasmodium falciparum. - Rohrbach, Petra; Sanchez, Cecilia P; Hayton, Karen; Friedrich, Oliver; Patel, Jigar; Singh Sidhu, Amar Bir; Ferdig, Michael T; Fidock, David A; Lanzer, Michael (EMBO Journal, 2006)
The P-glycoprotein homolog of the human malaria parasite Plasmodium falciparum (Pgh-1) has been implicated in decreased susceptibility to several antimalarial drugs, including quinine, mefloquine and artemisinin. Pgh-1 mainly resides within the parasite's food vacuolar membrane. Here, we describe a surrogate assay for Pgh-1 function based on the subcellular distribution of Fluo-4 acetoxymethylester and its free fluorochrome. We identified two distinct Fluo-4 staining phenotypes: preferential staining of the food vacuole versus a more diffuse staining of the entire parasite. Genetic, positional cloning and pharmacological data causatively link the food vacuolar Fluo-4 phenotype to those Pgh-1 variants that are associated with altered drug responses. On the basis of our data, we propose that Pgh-1 imports solutes, including certain antimalarial drugs, into the parasite's food vacuole. The implications of our findings for drug resistance mechanisms and testing are discussed.